Post-antibiotic era in hemodialysis? Two case reports of simulta- neous colonization and bacteremia by multidrug-resistant bacteria (2021)
ABSTRACT : The emergence of resistance mechanisms not only limits the therapeutic options for common bacterial infections but also worsens the prognosis in patients who have conditions that increase the risk of bacterial infections. Thus, the effectiveness of important medical advances that seek to improve the quality of life of patients with chronic diseases is threatened. We report the simultaneous colonization and bacteremia by multidrug-resistant bacteria in two hemodialysis patients. The first patient was colonized by carba-penem- and colistin-resistant Klebsiella pneumoniae, carbapenem-resistant Pseu-domonas aeruginosa, and methicillin-re-sistant Staphylococcus aureus (MRSA). The patient had a bacteremia by MRSA, and molecular typing methods confirmed the colonizing isolate was the same strain that caused infection. The second case is of a patient colonized by extended-spec-trum beta-lactamases (ESBL)-producing Escherichia coli and carbapenem-resis-tant Pseudomonas aeruginosa. During the follow-up period, the patient presen-ted three episodes of bacteremia, one of these caused by ESBL-producing E. coli. Molecular methods confirmed colonization by the same clone of ESBL producing E. coli at two time points, but with a different genetic pattern to the strain isolated from the blood culture. Colonization by multidrug-resistant bacteria allows not only the spread of these microorganisms, but also increases the subsequent risk of infections with limited treatments options. In addition to infection control measures, it is important to establish policies for the prudent use of antibiotics in dialysis units.